A Qualitative Case Study on the Use of Balance Scorecard to Control Performance of a Local Government-Owned Water Supply Company in Indonesia (Journal of Business Management and Accounting, 2016)
This paper discusses how the Balance Scorecard is applied in a water supply company in Indonesia. The company investigated in this study was a local government-owned water supply company is responsible for generating profit, as well as having a social function.  Performance  becomes  an  important  issue  in  this  type  of  company,  not  just from the financial aspect, but also regarding non-financial performance. This research was  a  longitudinal  case  study.  By  applying  ethnography,  the  researcher  participated in  the  process  of  controlling  performance  while  performing  the  research,  where  the case company modified the four perspectives of Balance Scorecard into four aspects of performance, i.e., financial, service, operational, and human resource performance aspects. This modified balance scorecard was used to control people in achieving their targeted performance. A management control system model was then used as a tool and mechanism to control performance.